Verruciform xanthoma of the lip: A rarity - Treville Pereira; Subraj Shetty; Shashibhushan Dodal; Avinash Tamgadge (Wolters Kluwer Medknow Publications, 2016)
Verruciform xanthoma (VX) is an uncommon, benign, asymptomatic mucocutaneous lesion of an unknown etiopathology. It usually presents as a papule or single plaque with a verrucous or a papillomatous surface and pale yellowish to red in color. It occurs primarily on the masticatory mucosa of middle-aged individuals. We report a case of VX on the lip of a 59-year-old man. Histopathologically, VX is diagnosed by the presence of foam cells in the papillary region of the connective tissue. Differentiating a verrucous carcinoma from VX is important, especially in small superficial lesions, which may lead to inappropriate and excessive surgical intervention. Treatment of VX consists of simple surgical excision and recurrence is rare.